Association Between Lymphedema Self-Care Adherence and Lymphedema Outcomes Among Women with Breast Cancer-Related Lymphedema. (April 2015) - Brown, Justin C.; Kumar, Anagha; Cheville, Andrea L.; Tchou, Julia C.; Troxel, Andrea B.; Harris, Susan R.; Schmitz, Kathryn H.
ABSTRACT: Objective: The aim of this study was to determine whether adherence to self-care modalities for breast cancer-related lymphedema (BCRL) predicts BCRL outcomes among 128 breast cancer survivors who participated in the 12-mo physical activity and lymphedema trial. Design: This was a prospective cohort study. Adherence to ten BCRL self-care modalities, as recommended in the clinical practice guidelines for the management of BCRL, was assessed by a questionnaire at baseline. BCRL outcomes assessed at baseline and 12 mos included volumetry, circumferences, bioimpedence spectroscopy, the Norman lymphedema survey, and therapist-defined lymphedema exacerbations requiring treatment. Generalized linear models were used to estimate the relationship between adherence to BCRL self-care modalities and the likelihood of experiencing a BCRL outcome. Results: Adherence to BCRL self-care activities did not predict experiencing any BCRL outcomes at 12 mos. Levels of adherence to BCRL self-care modalities did not predict a 5% or greater decrease in interlimb volume ( P trend = 0.79), 5% or greater decrease in the sum of interlimb arm circumferences ( P trend = 0.47), 10% or greater decrease in bioimpedence spectroscopy ( P trend = 0.83), 1 or greater decrease in self-reported lymphedema symptoms ( P trend = 0.91), or therapist-defined lymphedema exacerbation requiring treatment ( P trend = 0.84). Conclusions: Our findings suggest that levels of BCRL self-care adherence do not predict BCRL outcomes among breast cancer survivors with stable lymphedema who were followed for 12 mos.